Icariin alleviates osteoarthritis by inhibiting NLRP3-mediated pyroptosis - Yan Zu (Journal of Orthopaedic Surgery and Research, 2019)
Abstract Background Osteoarthritis (OA) is the common chronic degenerative joint bone disease that is mainly featured by joint stiffness and cartilage degradation. Icariin (ICA), an extract from Epimedium, has been preliminarily proven to show anti-osteoporotic and anti-inflammatory effects in OA. However, the underlying mechanisms of ICA on chondrocytes need to be elucidated. Methods LPS-treated chondrocytes and monosodium iodoacetate (MIA)-treated Wistar rats were used as models of OA in vitro and in vivo, respectively. LDH and MTT assays were performed to detect cytotoxicity and cell viability. The expression levels of NLRP3, IL-1β, IL-18, MMP-1, MMP-13, and collagen II were detected by qRT-PCR and Western blotting. The release levels of IL-1β and IL-18 were detected by ELISA assay. Caspase-1 activity was assessed by flow cytometry. Immunofluorescence and immunohistochemistry were used to examine the level of NLRP3 in chondrocytes and rat cartilage, respectively. The progression of OA was monitored with hematoxylin-eosin (H&E) staining and safranin O/fast green staining. Results ICA could suppress LPS-induced inflammation and reduction of collagen formation in chondrocytes. Furthermore, ICA could inhibit NLRP3 inflammasome-mediated caspase-1 signaling pathway to alleviate pyroptosis induced by LPS. Overexpression of NLRP3 reversed the above changes caused by ICA. It was further confirmed in the rat OA model that ICA alleviated OA by inhibiting NLRP3-mediated pyroptosis. Conclusion ICA inhibited OA via repressing NLRP3/caspase-1 signaling-mediated pyroptosis in models of OA in vitro and in vivo, suggesting that ICA might be a promising compound in the treatment of OA.